2015
DOI: 10.1021/acs.chemmater.5b03564
|View full text |Cite
|
Sign up to set email alerts
|

Proper Ferroelectricity in the Dion–Jacobson Material CsBi2Ti2NbO10: Experiment and Theory

Abstract: A diverse range of materials and properties are exhibited by layered perovskites. We report on the synthesis, characterization, and computational investigation of a new ferroelectricCsBi2Ti2NbO10an n = 3 member of the Dion–Jacobson (DJ) family. Structural studies using variable-temperature neutron powder diffraction indicate that a combination of octahedral rotations and polar displacements result in the polar structure. Density functional theory calculations reveal that the wider perovskite blocks in CsBi2T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 66 publications
6
51
1
Order By: Relevance
“…17 This understanding allowed us to tune the chemistry of the RP2 solid solution Ca 3−3x Sr 3x Mn 2 O 7 in the phase diagram space to precisely control its NTE. 18 Very recently NTE has also been reported in the n = 1 (RP1) compound Sr 2 19 our explanation for NTE in the RP2 phase directly implicates specific soft phonon modes of RUM-like character with negative Grüneisen parameters. This understanding from prior publications leaves us with the question: (i) If NTE originates from octahedral rotations of RUM character, why is similar NTE not observed in equivalent bulk ABO 3 perovskite phases?…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…17 This understanding allowed us to tune the chemistry of the RP2 solid solution Ca 3−3x Sr 3x Mn 2 O 7 in the phase diagram space to precisely control its NTE. 18 Very recently NTE has also been reported in the n = 1 (RP1) compound Sr 2 19 our explanation for NTE in the RP2 phase directly implicates specific soft phonon modes of RUM-like character with negative Grüneisen parameters. This understanding from prior publications leaves us with the question: (i) If NTE originates from octahedral rotations of RUM character, why is similar NTE not observed in equivalent bulk ABO 3 perovskite phases?…”
Section: Introductionmentioning
confidence: 54%
“…Due to their unusual lattice couplings and dynamics, there has been renewed recent interest in tuning the properties of layered materials based on the perovskite structure, including proper, 1,2 and improper, [3][4][5] ferroelectricity, the electrocaloric effect, 6 and colossal magnetoresistance. 7 Unprecedented control of ferroelectricity in layered perovskites has been achieved, for example, by engineering non-polar lattice instabilities that can combine in the ground state to produce a net polarisation.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we demonstrate that ferroelectricity emerges by layering nonpolar perovskite SrZrO 3 with nonpolar rock salt‐structured SrO to form the n = 2 Ruddlesden–Popper (RP) A 3 B 2 O 7 structure . We show that Sr 3 Zr 2 O 7 is a hybrid improper ferroelectric (HIF), whereby ferroelectricity with an electric polarization P occurs from a combination of two nonpolar lattice modes, Q 1 and Q 2 , interacting through a trilinear term of the form PQ 1 Q 2 . The role played by the two nonpolar structural distortions—oxygen octahedral rotations (OOR, out‐of‐plane rotational modes) and oxygen octahedral tilts (OOT, in‐plane rotational modes)—in stabilizing ferroelectricity is determined using a combination of synchrotron X‐ray diffraction (SXRD), neutron powder diffraction (NPD), optical second harmonic generation (SHG), and first‐principles density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 88%
“…Although the a − a − c + tilt system is predicted to be a stable option for DJ phases of the type AA'B 2 O 7 , recent experimental work has shown that other related polymorphs are possible, and a tilt system a − b 0 c + , in polar space group Amm2, has been reported in CsLaNb 2 O 7 in the range 350 < T < 550 K [12] (curiously an earlier single crystal X-ray study of CsLaNb 2 O 7 reported the adoption of the aristotype tetragonal structure, P4/mmm at 296 K [13]). Moreover, a recent experimental and theoretical study of the triple-layer DJ phase CsBi 2 Ti 2 NbO 10 has suggested that a proper rather than improper mechanism drives the polarity of the ambient temperature phase [14]. It is therefore of interest to explore more fully the phase behavior of further examples of the DJ family in order to map out the occurrence of the possible tilt systems, especially those giving rise to polarity, and also the nature of phase transitions in these systems as a function of T.…”
Section: Introductionmentioning
confidence: 99%